Role of CO 2 and Southern Ocean winds in glacial abrupt climate change - M. Montoya; J. Álvarez-Solas; R. Banderas (Climate of the Past, 2012)
The study of Greenland ice cores revealed two decades ago the abrupt character of glacial millennial-scale climate variability. Several triggering mechanisms have been proposed and confronted against growing proxy-data evidence. Although the implication of North Atlantic deep water (NADW) formation reorganisations in glacial abrupt climate change seems robust nowadays, the final cause of these reorganisations remains unclear. Here, the role of CO 2 and Southern Ocean winds is investigated using a coupled model of intermediate complexity in an experimental setup designed such that the climate system resides close to a threshold found in previous studies. An initial abrupt surface air temperature (SAT) increase over the North Atlantic by 4 K in less than a decade, followed by a more gradual warming greater than 10 K on centennial timescales, is simulated in response to increasing atmospheric CO 2 levels and/or enhancing southern westerlies. The simulated peak warming shows a similar pattern and amplitude over Greenland as registered in ice core records of Dansgaard-Oeschger (D/O) events. This is accompanied by a strong Atlantic meridional overturning circulation (AMOC) intensification. The AMOC strengthening is found to be caused by a northward shift of NADW formation sites into the Nordic Seas as a result of a northward retreat of the sea-ice front in response to higher temperatures. This leads to enhanced heat loss to the atmosphere as well as reduced freshwater fluxes via reduced sea-ice import into the region. In this way, a new mechanism that is consistent with proxy data is identified by which abrupt climate change can be promoted.